2019
DOI: 10.1371/journal.pone.0212763
|View full text |Cite
|
Sign up to set email alerts
|

The role of the erythrocyte in the outcome of pregnancy with preeclampsia

Abstract: The objective of this study was to analyze the relationships of osmotic and mechanical stability of erythrocytes with anthropometric, biochemical, hematologic and hemodynamic variables in pregnant women with preeclampsia (PE). The studied population consisted of 20 normotensive patients and 16 patients with PE. Patients with PE presented worse gestational outcome, greater hematologic impairment, erythrocytes osmotically more stable in vitro , but in conditions of isotonicity with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…In the population studied here, the RDW increases under the simultaneous influence of a factor associated with volume increase (reticulocyte) and other factors associated with volume decrease (lower iron levels) 50 . As RDW represents heterogeneity in the volume distribution of erythrocytes, this explains why, then, RDW was not correlated with MCV (Figure 3), although a positive correlation between those variables was reported in patients who underwent bariatric surgery 29 and a negative correlation has been found in pregnant women with pre‐eclampsia 28 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the population studied here, the RDW increases under the simultaneous influence of a factor associated with volume increase (reticulocyte) and other factors associated with volume decrease (lower iron levels) 50 . As RDW represents heterogeneity in the volume distribution of erythrocytes, this explains why, then, RDW was not correlated with MCV (Figure 3), although a positive correlation between those variables was reported in patients who underwent bariatric surgery 29 and a negative correlation has been found in pregnant women with pre‐eclampsia 28 …”
Section: Discussionmentioning
confidence: 99%
“…The near NaCl concentrations where lysis begins (H0) and ends (H100) were then determined according to the following equations: and as previously described. 28 Amin, H 0 , H 50 and H 100 are osmotic fragility variables and therefore have inverse relationships with the erythrocyte osmotic stability, but dX is effectively a stability variable; that is, dX increases with increasing osmotic stability of these cells.…”
Section: Determination Of Erythrocyte Osmotic Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent publication analyzing the osmotic and mechanical stability of erythrocytes, it is suggested that erythrocytes with lower volume and lower hemoglobin content are osmotically more stable. They assumed that lower MCV values could be a mechanism of compensatory mechanical selection, which is be-neficial in PE [19]. However, the desired range of MCV throughout pregnancies complicated by PE remains unclear.…”
Section: Routinely Measured Rbc Laboratory Parametersmentioning
confidence: 99%
“…Al-Zamely and Falh [7] reported that treatment with 1×10 9 CFU/mL of E. coli decreases the hemoglobin concentration, caused by a breakdown of erythrocytes by hemolysis enzymes produced by E. coli. A decrease in erythrocytes during pregnancy results in anemia resulting from a short erythrocyte life span [8]. Bacterial infections can produce adverse effects on the erythrocyte lineage and hormone levels during pregnancy [2].…”
Section: Introductionmentioning
confidence: 99%